Runx2 rs59983488 polymorphism in class II malocclusion in the Indonesian subpopulation - Fadli Jazaldi; Benny M. Soegiharto; Astrid Dinda Hutabarat; Noertami Soedarsono; Elza Ibrahim Auerkari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Class II malocclusion is one of the main orthodontic issues for patients in seeking treatment. The prevalence of class II malocclusion varies in different populations. Variation in skeletal profile is mainly controlled internally by a regulatory gene. Runt-related transcription factor-2 (Runx2) plays a role in osteoblast differentiation and is highly expressed during development. Purpose: This study aimed to evaluate the relation of regulatory gene variation in the Runx2 promoter with class II malocclusion. Methods: DNA samples were acquired from 95 orthodontic patients in Jakarta, Indonesia, who were divided into two groups: class I skeletal malocclusion (control group) and class II malocclusion. A single nucleotide polymorphism was investigated using the polymerase chain reaction and restriction fragment length polymorphism techniques. The distribution of alleles was assessed using the Hardy-Weinberg test. The relationship between polymorphism and skeletal variation was assessed with the Chi-Square test and logistic regression. Results: The frequency distributions of genotypes and alleles were tested for Hardy-Weinberg equilibrium and found to be slightly deviated. There was an equal distribution of G and T alleles throughout class II and class I skeletal malocclusions and the Chi-Square test showed that this relationship was not significant (p=0.5). Conclusion: Runx2 rs59983488 polymorphism was found in the Indonesian subpopulation; however, an association between Runx2 rs59983488 polymorphism and class II skeletal malocclusion was not found.